Dose Response of Weed Seeds, Plant-Parasitic Nematodes, and Pathogens to Twelve Rates of Metam Sodium in a California Soil - Klose, Susanne (Plant disease, 2008)
Metam sodium (sodium N-methyl dithiocarbamate, metam-Na) is widely used in agricultural and floricultural production for controlling soilborne plant pathogens, parasitic nematodes, and weeds. It undergoes rapid decomposition to the biocide methyl isothiocyanate (MITC) in moist soils. In this study, the efficacy of 12 concentrations of metam-Na (10 to 2,650 μmol kg-1 soil) to control seeds or tubers of five major weed species, three soilborne pathogens, and one parasitic nematode was evaluated in a sandy loam soil under controlled conditions. Soils were exposed to the fumigant in microcosms for 24 h at 10 and 20°C. Generation and dissipation curves of MITC in soil under controlled conditions showed that MITC concentrations in soils were highest 2 h after metam-Na application and decreased steadily over the 24-h incubation period. After 24 h, remaining MITC concentrations in soil microcosms at 10 and 20°C were 53 and 38% of the original amount applied, respectively, indicating a 20% reduction in MITC dissipation at the lower soil temperature. Logistic dose-response models were used to estimate the effective concentration necessary to reduce soil pest viability by 50 (LC50) or 90 (LC90) percent under both temperatures. Seed of Portulaca oleracea, with LC90 values of ≤1,242 μmol kg-1 soil, was the most sensitive to soil fumigation with metam-Na, followed by Polygonum arenastrum with LC90 values of ≤1,922 μmol kg-1 soil. At 10°C fumigation temperature, metam-Na at the highest dose tested in this study, 2,650 μmol kg-1 soil, was not sufficient to achieve adequate control of Stellaria media and Malva parviflora seed and Cyperus esculentus tubers. Weed control efficacy (average reduction in LC90 values) of metam-Na was between 25 and 60% higher if soils were fumigated at 20°C compared with 10°C, with the exception of M. parviflora. Phytophthora cactorum and Pythium ultimum were more sensitive to soil fumigation with metam-Na (LC90 ≤ 165 μmol kg-1 soil) than Verticillium dahliae (LC90 ≤ 737 μmol kg-1 soil). The nematode Tylenchulus semipenetrans was highly sensitive to soil fumigation with metam-Na (LC90 ≤ 98 μmol kg-1 soil), and the efficacy of control increased by 30% if soil was fumigated at 20°C compared with 10°C. In this sandy loam soil, metam-Na at a concentration of 850 μmol kg-1 reduced the viability of Portulaca oleracea and Polygonum arenastrum seeds, C. esculentus tubers, and all soilborne pathogens and parasitic nematodes tested by 90% at 20°C after 24 h exposure. These results indicate that metam-Na can provide effective pest and disease control at maximum label rate for the commercial formulation, but there was a reduction in efficacy at low temperature